Proteinus crenulatus - a complex of five species (Coleoptera: Staphylinidae: Proteininae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2007)
A revision of types and additional material revealed that what has previously been interpreted as Proteinus crenulatus Pandellé, 1867 is in fact a complex of five similar species: P. crenulatus (widespread in Europe), P. abditus sp. n. (Germany, Romania), P. hamatus sp. n. (N-Spain, SW-France), P. tronqueti sp. n. (Corsica), and P. angulatus sp. n. (S-Italy, S-Greece). The distinguishing characters are described and illustrated. A lectotype is designated for P. crenulatus Pandellé. The distributions of all five species are mapped. Keywords Coleoptera, Staphylinidae, Proteininae, Proteinus, Western Palaearctis, taxonomy, lectotype designation. Nomenclatural Acts abditus Assing, 2007 (Proteinus), spec. n. angulatus Assing, 2007 (Proteinus), spec. n. crenulatus Pandellé, 1867 (Proteinus), Lectotype hamatus Assing, 2007 (Proteinus), spec. n. tronqueti Assing, 2007 (Proteinus), spec. n.